Pre-service Teachers’ Perceptions on Internship in Relation to Integrated and Specific Professional Teaching Courses: A Study - Mohapatra, Animesh Kumar; Deepshikha,; Priyamvada, (Voices of Teachers and Teacher Educators, 2022)
Internship has an essential role in developing the teaching competency of the pre-service teachers. The objective of this research was to explore the perceptions of teachers under training towards various aspects of internship. Further this study also aimed to compare the perspectives of student teachers enrolled in 4-year integrated and two year specific professional courses. The sample included 250 student teachers from Regional Institute of Education, Bhubhaneswar who had recently completed their internship. Out of 250 students, 150 were from 4-year integrated courses and 100 were from two year courses. Purposive sampling was used for this study. The data collection and analysis revealed that most of the student teachers agreed to the fact that internship is very important as a part of any teachers’ training program. Further the findings of the study revealed that there were significant differences in the perceptions of student teachers of integrated and specific courses with respect to appropriateness of duration of internship, number of lesson plans assigned, practice of teaching skills and use of ICT in classroom during internship.